2004
DOI: 10.1074/jbc.m308177200
|View full text |Cite
|
Sign up to set email alerts
|

The 5-Hydroxytryptamine(1A) Receptor Is Stably Palmitoylated, and Acylation Is Critical for Communication of Receptor with Gi Protein

Abstract: In the present study, we verified that the mouse 5-hydroxytryptamine(1A) (5-HT 1A ) receptor is modified by palmitic acid, which is covalently attached to the protein through a thioester-type bond. Palmitoylation efficiency was not modulated by receptor stimulation with agonists. Block of protein synthesis by cycloheximide resulted in a significant reduction of receptor acylation, suggesting that palmitoylation occurs early after synthesis of the 5-HT 1A receptor. Furthermore, pulse-chase experiments demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
79
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 68 publications
8
79
0
1
Order By: Relevance
“…Furthermore, we found that the glycosylation state and the ligand-binding capacity of 5-HT 1A R were not dependent on the presence of the palmitoylated cysteines. These data are consistent with results obtained by Papoucheva et al (Papoucheva et al, 2004) who recently demonstrated the constitutive palmitoylation of cysteines 417 and 420 of this receptor. These authors also showed that palmitoylated cysteines 417 and 420 are necessary for the receptor coupling to G ␣i3 subunit in transfected insect Sf.9 cells, as well as for its capacity to inhibit adenylyl cyclase activity in NIH3T3 cells and to activate ERK in CHO cells.…”
Section: Journal Of Cell Science 119 (20)supporting
confidence: 94%
See 2 more Smart Citations
“…Furthermore, we found that the glycosylation state and the ligand-binding capacity of 5-HT 1A R were not dependent on the presence of the palmitoylated cysteines. These data are consistent with results obtained by Papoucheva et al (Papoucheva et al, 2004) who recently demonstrated the constitutive palmitoylation of cysteines 417 and 420 of this receptor. These authors also showed that palmitoylated cysteines 417 and 420 are necessary for the receptor coupling to G ␣i3 subunit in transfected insect Sf.9 cells, as well as for its capacity to inhibit adenylyl cyclase activity in NIH3T3 cells and to activate ERK in CHO cells.…”
Section: Journal Of Cell Science 119 (20)supporting
confidence: 94%
“…This would suggest the need for another signal localized in a different domain of the receptor in addition to the di-leucine motif of the C-terminal tail, which would be present in the 5-HT 1A R but not in the 5-HT 1B R, thereby leading to plasma membrane targeting of the 1ActB but not the 1BctA chimera. Alternatively, it is possible Role of palmitoylated cysteines 5-HT 1A R and 5-HT 1B R were shown to contain palmitoylated cysteines in their C-terminal domain (Ng et al, 1993;Papoucheva et al, 2004). Substitution of these residues with serines did not affect the subcellular localization of either receptors or chimeras.…”
Section: Journal Of Cell Science 119 (20)mentioning
confidence: 99%
See 1 more Smart Citation
“…The C-terminal domain of the 5-HT1A receptor also seems to be critical for coupling to both G␣ i and G␤␥ pathways. Unlike other receptors, the 5-HT1A receptor is constitutively palmitoylated at C-terminal cysteine residues (417 and 420), and palmitoylation is required for coupling to G i (i.e., loss of inhibition of AC activity) and G␤␥-mediated activation of extracellular signal-regulated kinases (Papoucheva et al, 2004). Thus, Ci2, Ni3, Ci3, and palmitoylated 5-HT1A C-terminal domains seem critical for G-protein coupling and may directly interact to form a Gprotein coupling interface.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the T149A residue of the Ci2 domain plays a crucial role in G␤␥-induced pathways of the 5-HT1A receptor. In addition to the i2 domain, the i3 and palmitoylated C-terminal domains of the 5-HT1A receptor have also been implicated in G-protein coupling (Varrault et al, 1994;Sun and Dale, 1999;Papoucheva et al, 2004;Turner et al, 2004). Peptides derived from the Ni3 or Ci3 domains of the 5-HT1A receptor can mimic G␣ i -mediated inhibition of adenylyl cyclase, whereas i2 peptides prevented this coupling (Varrault et al, 1994;Ortiz et al, 2000).…”
mentioning
confidence: 99%